2022
DOI: 10.3390/jcm11237175
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Is a Contributing Factor of Low Appendicular Lean Mass in Older Community-Dwelling Women: A Cross-Sectional Study

Abstract: Inflammation is a chronic, sterile, low-grade inflammation that develops with advanced age in the absence of overt infection and may contribute to the pathophysiology of sarcopenia, a progressive and generalized skeletal muscle disorder. Furthermore, a series of biomarkers linked to sarcopenia occurrence have emerged. To aid diagnostic and treatment strategies for low muscle mass in sarcopenia and other related conditions, the objective of this work was to investigate potential biomarkers associated with appen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…A UK cohort study including 336 community-dwelling elderly men and women demonstrated that an elevated IL-8 level was associated with an increased risk of sarcopenia (Oflazoglu et al, 2020 ). Consistent with this, several clinical studies have shown that sarcopenia in the elderly had higher levels of IL-8 compared with the non-sarcopenia group (Fan et al, 2022 ; Teixeira et al, 2022 ). Interestingly, IL-8 is also identified as a biomarker during AD progression (Swardfager et al, 2010 ; Alsadany et al, 2013 ).…”
Section: Potential Mechanisms Of Skeletal Muscle–brain Crosstalk In C...supporting
confidence: 54%
“…A UK cohort study including 336 community-dwelling elderly men and women demonstrated that an elevated IL-8 level was associated with an increased risk of sarcopenia (Oflazoglu et al, 2020 ). Consistent with this, several clinical studies have shown that sarcopenia in the elderly had higher levels of IL-8 compared with the non-sarcopenia group (Fan et al, 2022 ; Teixeira et al, 2022 ). Interestingly, IL-8 is also identified as a biomarker during AD progression (Swardfager et al, 2010 ; Alsadany et al, 2013 ).…”
Section: Potential Mechanisms Of Skeletal Muscle–brain Crosstalk In C...supporting
confidence: 54%
“…Inflammatory biomarkers that indicate muscle catabolism are highly correlated with frailty in multimorbid patients 38 , and previous studies have associated adiponectin levels with reduced appendicular muscle mass independent of body fat in older women 39 . It is crucial to consider the algorithm employed in our sample for evaluating screening procedures based on handgrip strength, being muscle mass or physical performance is a secondary component in determining Sarcopenia.…”
Section: Discussionmentioning
confidence: 94%
“…On the third visit, which took place 24 h after the body composition and physical tests, blood samples were collected from the participants for the analysis of inflammatory biomarkers. Sampling information and procedures is also available in elsewhere 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%